19. DISTRIBUTION OF GROUP B STREPTOCOCCUS SEROTYPE III AMONG PREGNANT WOMEN IN HANOI (Vietnam Journal of Community Medicine, 2024)
Objectives: We investigated the distribution of Group B Streptococcus (GBS) serotype III among pregnant women in Hanoi, and its association with other factors.Methods: A cross-sectional study was conducted on 876 pregnant women at a gestational age of 35–37 weeks in three hospitals in Hanoi, Vietnam from October 2021 to May 2022. Vaginal-rectal samples were collected to screen GBS using culture and PCR methods. PCR techniques were also used to analyze the serotypes of GBS strains. The data were analyzed to determine the prevalence of serotype III and its relationship to other factors.Results: Of the 171 GBS isolates, 40 strains (23.39%) were identified as serotype III, accounting for the highest prevalence. The age group of 30 to under 35 years had the largest number of serotype III infections. Pregnant women infected with serotype III (32.5%) had a slightly higher prevalence of genitourinary tract infections (GTIs) history than those infected with other serotypes (28.24%).Conclusion: Serotype III is the predominant GBS serotype among GBS isolates from pregnant women in Hanoi. Further research is needed to explore the immune response mechanisms and the impact of serotype III on maternal and neonatal outcomes.
Keywords: Group B Streptococcus; serotype III